What is so unappealing about blue food and drink? - Spence, C (Elsevier, 2018)
During the latter half of the last century, a number of cultural commentators confidently asserted that blue food and drink products would never succeed in the marketplace. How, then, to explain the recent rise of blue drinks in our stores and images of blue foods online? Blue foods are certainly rare in nature, rarer, at least, than foods of other colours. Perhaps as a result, this hue tends to be associated with notions of unnatural and artificial food colouring. That said, ‘natural’ blue food and drink items are becoming an increasingly common sight in the grocery aisles and online due, in part, to this colour’s ability to capture our attention in-amongst the other more common food colours. This article highlights those situations/contexts in which blue is/isn’t an acceptable food colour, and how attitudes have changed over the decades, in part, due to the emergence of a number of naturally-sourced colouring agents. Ultimately, I consider the question of what, if anything, is stopping us from purchasing/making/consuming more blue food and drink products, and whether or not the current popularity of this colour will last. This review also addresses the question of why it is that blue foods are so rarely seen in chef-prepared meals.